Assessing the risk of insecticides to Actinopterygii in the combination of ecological planting and rearing. (1st May 2021) - Wang, Dongsheng; Lv, Weiguang; Yuan, Yongda; Zhang, Tianshu; Teng, Haiyuan; Losey, John E.; Chang, Xiaoli
Abstract: In order to study the co-existing environment of pests and economic animals, the toxicity of 15 insecticides to Plutella xylostella, Monopterus albus, and Paramisgurnus dabryanus was tested. Combined with the recommended maximum doses in the field and bioassay, the results showed that for the three insecticides that were of relatively low toxicity to M. albus and P. dabryanus, spinetoram showed the best control effect on P. xylostella, followed by chlorfenapyr and chlorantraniliprole. However, P. xylostella showed a relatively high resistance to chlorfenapyr. Therefore, the best insecticide suitable for the fields with the cauliflower-finless eel or cauliflower-loach planting and rearing combination was spinetoram, followed by chlorantraniliprole and chlorfenapyr. Other insecticides such as emamectin benzoate, Bacillus thuringiensis (Bt), matrine, and so on were effective against the diamondback moth, but they were not suitable for use because of their high toxicity to the finless eel and loach. Graphical abstract: Image 1 Highlights: Pesticide problems in the combination of ecological planting and rearing. Spinetoram, chlorantraniliprole, and chlorfenapyr showed good control effects. Spinetoram, chlorfenapyr, and chlorantraniliprole exerted lower toxicity effects. P. xylostella showed the highest resistance to chlorfenapyr. The best insecticides were spinetoram, chlorantraniliprole, and chlorfenapyr. Abstract : The best insecticide suitable for the fields with the cauliflower-finless eel or cauliflower-loach combination was spinetoram, followed by chlorantraniliprole and chlorfenapyr.